Peran Persepsi Harga, Ekuitas Merek dan Kualitas Produk Terhadap Keputusan Pembelian Sepeda Motor Vario 150 CC Di Kabupaten Kebumen - Surono; Rizana, D (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2023)
This research aims to find out the role of price perception, brand equity, product quality on purchasing decisions. The subject of this research is the Vario 150 CC product which was carried out in Kebumen district. The number of samples used in this research was 100 respondents who used Vario 150 CC motorbikes using incidential techniques. The research results show that: partially price perception has a significant influence on purchasing decisions, partially brand equity influences purchasing decisions, partially product quality influences purchasing decisions, and simultaneously price perception, brand equity and product quality jointly influence purchasing decisions, it can be concluded that together the variables of price perception, brand equity and product quality have a significant influence on purchasing decisions.